Address at the Annual Dinner of the Connecticut Chamber of Commerce - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, spoke about underdeveloped areas of the world and the role of World Bank on those areas. He focused on the role of trade in developed and developing countries and its implications for their economic development. He explained the role of the Bank in encouraging participation of private capital in international investment.